Quercetin improves and protects Calu-3 airway epithelial barrier function - DiGuilio, K. M.; Rybakovsky, E.; Valenzano, M. C.; Nguyen, H. H.; Del Rio, E. A.; Newberry, E.; Spadea, R.; Mullin, J. M. (Frontiers in Cell and Developmental Biology, 2023)
Introduction: In light of the impact of airway barrier leaks in COVID-19 and the significance of vitamin D in COVID-19 outcomes, including airway barrier protection, we investigated whether the very common dietary flavonoid quercetin could also be efficacious in supporting airway barrier function. Methods: To address this question, we utilized the widely used airway epithelial cell culture model, Calu-3. Results: We observed that treating Calu-3 cell layers with quercetin increased transepithelial electrical resistance while simultaneously reducing transepithelial leaks of 14C-D-mannitol (Jm) and 14C-inulin. The effects of quercetin were concentration-dependent and exhibited a biphasic time course. These effects of quercetin occurred with changes in tight junctional protein composition as well as a partial inhibition of cell replication that resulted in decreased linear junctional density. Both of these effects potentially contribute to improved barrier function. Quercetin was equally effective in reducing the barrier compromise caused by the pro-inflammatory cytokine TNF-α, an action that seemed to derive, in part, from reducing the elevation of ERK 1/2 caused by TNF-α. Discussion: Quercetin improved Calu-3 barrier function and reduced TNF-α-induced barrier compromise, mediated in part by changes in the tight junctional complex.